Diversity of insect pests and natural enemies as influenced by growth stages and pest management practices in rice (Bangladesh Journal of Agricultural Research, 2016)
In order to measure the diversity of insect pests and natural enemies in rice ecosystem, the present study was conducted in the research farm of Patuakhali Science and Technology University, Dumki, Patuakhali during the period from January to June, 2012 in boro rice season. Diversity indices of insect pests and their natural enemies were found to be affected by the combined effect of rice growth stages and management practices. Diversity indices of insect pests and their natural enemies differed according to treatments and crop growth stages. In case of insect pests, the untreated control treatment showed the highest diversity index (1.67) at maximum tillering stage and spray (Bipolar 55EC @ 10 ml/10 L of water) + perching at early tillering stage also showed highest richness (26.14) and the highest evenness (0.921) in spray at seedling stage. The highest reciprocal form of Berger-Parker's Dominance index (D) was found in untreated control at maximum tillering stage (3.03) for insect pests. In case of natural enemies, perching showed the highest diversity index (1.88) at reproductive stage. Spraying of insecticide at early tillering stage also showed highest richness (5.06) and the highest evenness (0.982) was in perching at seedling stage. The highest D value was found in perching at reproductive stage (4.67) for natural enemies.Bangladesh J. Agril. Res. 41(3): 461-470, September 2016